Minimally Invasive Central Cannulation for Extracorporeal Life Support: The Uniportal and Subxiphoid Approach. Issue 6 (November 2022) - Durak, Koray; Rizk, Dana; Emunds, Janina; Vorwold, Felix; Kalverkamp, Sebastian; Steinseifer, Ulrich; Strudthoff, Lasse; Spillner, Jan; Hima, Flutura
Objective: Extracorporeal life support (ECLS) for circulatory and/or respiratory failure is improving. Currently, invasive sternotomies or rib-spreading thoracotomies are used for central cannulation of the heart and great vessels. Although peripheral cannulation of the extremities is often used, this approach may result in immobility and unintentional dislodgement. Less invasive methods for central cannulation are needed to achieve long-term ECLS. The objective of this study was to develop 2 different minimally invasive approaches for central thoracic cannulation. Methods: Porcine hearts were positioned in a plastic thoracic model. An endoscopic camera and multiple endoscopic instruments were used. Both access points, uniportal (lateral) and subxiphoidal, were simulatively investigated. A novel cannulation method using purse string sutures, a custom-made endoscopic puncture tool, guidewires, and dilator-assisted cannulas was developed. Simulations were tested in a closed circuit regarding leak tightness. Results: The uniportal approach allowed a cannulation of the aorta, inferior vena cava, right atrium, and main pulmonary artery. Cannulation of the right branches of the pulmonary artery and vein was also possible. From the subxiphoid approach, cannulation of the aorta, main pulmonary artery, and both atria were possible. Subsequent evaluation and leakage tests revealed no damage to the surrounding structures and tightly sealed cannulation sites. The uniportal approach was also successfully performed in a human cadaver to connect the aorta and right atrium with cannulas from the subxiphoidal space. Conclusions: Both uniportal and subxiphoid central cannulation of potential sites for ECLS were feasible. This study encourages further investigation and potential clinical translation of minimally invasive central organ support.